Penggunaan Metode Circuit Training untuk Meningkatkan Keterampilan Dribbling Pemain Sepakbola Coerver Coaching U-15 - Wahdi, Agung Hilmi; Adha, Arfa; Syaputra, Aidil; Lubis, Ade Evriansyah; Purwanto, Purwanto; Diyanto, Rahmad; Salsabilah, Salsabilah (Fakultas Pendidikan Olahraga dan Kesehatan, Universitas Pendidikan Indonesia, 2025)
Dribbling is a basic technique that must be mastered by every soccer player because it is an important component in the game of soccer. This study aims to determine the effect of dribbling training using the circuit training method on improving the dribbling skills of Coerver Coaching U-15 soccer players. The research method used is an experiment with a Control Group Pre-test and Post-test design. The population in this study was Coerver Coaching Bandung players, with a sample of 14 U-15 players selected using a purposive sampling technique. The research instrument used was a 2-meter slalom dribble test. The results showed that the group using the circuit training method experienced an average increase from 10.36 to 8.34, with a difference of 2.02. While the control group experienced an average increase from 10.41 to 9.41, with a difference of 0.99. Hypothesis testing using the t-test shows a t-count value of 10.27 t-table 2.45, which means there is a significant increase in the experimental group. Thus, it can be concluded that dribbling training using the circuit training method has a significant effect on improving the dribbling skills of Coerver Coaching U-15 soccer players.